A robust crosslinked polysiloxane-embedded nanofiber membrane for long-cycle lithium metal batteries. (1st May 2022) - Song, Xuan; Gui, Xuefeng; Liu, Lingli; Lin, Qiong; Li, Dongxia; Wang, Zhongxin; Lin, Qixin; Sun, Xiangfeng; Xue, Yuxin; Xu, Kai
Abstract: The shortcomings such as undesired severe lithium-dendrite growth and side-reactions impede the applications of lithium batteries. Investigation into the formation of uniform lithium-ion diffusion layers provides new insights into the suppression of dendrite growth and stabilization of lithium metal. Herein, cross-linked nanofibrous polysiloxane hybrid membranes (SHMs) are fabricated via simple processes involving the electrospinning of poly(vinylidene fluoride- co -hexafluoropropylene), vinyl-terminated polydimethylsiloxane, and functional cage silsesquioxanes. The functional polar groups on the SHMs impart lithiophilicity to the membranes, thus enabling them to form artificial solid electrolyte interfaces to guide uniform Li-ion flux distribution, ensure smooth lithium deposition, and fundamentally alter dendrite formation. In addition, the shear enhancement effect of polydimethylsiloxane 3D networks not only changes the surface morphology but also facilitates the migration of lithium ions. As a result, with the introduction of these SHMs, the Li||Li symmetric batteries were stabilized and thus able to maintain successive electrodeposition over 800 h at 0.5 mA cm −2 and the LiFePO4 ||Li cells exhibit a high capacity of 112 mAh g –1 and 96.7% capacity retention after 400 cycles at 2C. This work provides an effective strategy for the suppression of uncontrolled lithium dendrite formation and the enhancement of cycling performance. Graphical abstract: Image, graphical abstract